SELF-ESTEEM, SOCIAL SUPPORT, AND SELF-ACCEPTANCE IN FAMILIES OF SCHIZOPHRENIA - Kinanggi, Ratnasari (International Journal Multidisciplinary (IJMI), 2024)
Self-acceptance is something that is very important in life, even a person's level of self-acceptance can determine how he assesses or respects himself. A person's self-acceptance can also be determined by the presence or absence of social support they have received so far. In this regard, the aim to be achieved in this research is to scientifically prove the influence of self-esteem and social support on families of schizophrenia sufferers. The method in this research applies a quantitative approach with multiple regression analysis techniques. The research sample obtained was 43 respondents. Sampling was carried out using random sampling technique. The results of this study prove that there is a positive influence of self-esteem and social support on self-acceptance, although the influence of social support is not significant, and there is a joint positive influence of self-esteem and social support on self-acceptance